Improving Fault Tolerance to Radiation Effects in Integrated Systems - Neuberger, Gustavo; Kastensmidt, Fernanda; Reis, Ricardo (Anais do Workshop de Testes e Tolerância a Falhas (WTF); 2004: Anais do V Workshop de Testes e Tolerância a Falhas, 2004)
This paper describes the radiation effects in integrated systems and discusses some techniques to mitigate these effects. The main circuits analyzed are SRAM memories and SRAM-based FPGAs. New techniques used to protect these circuits against these effects are also proposed in this work. One of the presented techniques to protect FPGAs is based on a combination of Double Modular Redundancy (DMR) with Concurrent Error Detection (CED) that can reduce overheads comparing to Triple Modular Redundancy (TMR). In the case of SRAM memories, a technique based on the Reed-Solomon Code and Hamming Code was developed, as well as a tool to generate a core for fault-tolerance that minimizes the area cost of the code. Some results are presented.